LOUDSPEAKER BAN: HOW COMMUNICATION SHAPED ROTTEN TRADITIONAL VALUES IN BOGOR REGENCY INDONESIA - Tria Patrianti; Retnowati WD Tuti; Mawar Mawar (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Background. Throughout history, communication have been fundamental source of shaping values in community and society.  In Rumpin District of Bogor Regency, Indonesia, communities  in two villages namelyCipinang and Rabak have been shaped by communication delivered by their religious leaders and community figures related to loudspeaker ban. The biggest adherent anti-loudspeaker (ASPEK or Anti Speaker) community is in Jatinunggal Dusun or Hamlet in   Cipinang Village, Rumpin Districts. In the beginning,  of restriction loudspeaker had been found in the mosque.  It turned out that the anti the speaker applies in the place where television , tape player and radio and all anything associated with audio , like music also are not allowed because they are  still associated with the speaker. This study aims to seek better understanding how the communication has shaped the community‟s rotten traditional value about loudspeaker ban in the said villages. Method.    This research is conducted through qualitative approach as the goal was to receive spontaneous, rich, specific, and relevant answers to provide the material needed for thick description (Brinkmann & Kvale, 2015. P 192).  A meod for this study, semi-structured interviews were used because the focus of the study was to gain in-depth insights to the perceptions and feelings of the participants such as religious leaders, community figures, cadres, and district staff in both villages.  Results. Respect the ancestors seeming to be the glue of every community in Rabak and Cipinang Villages and it has been shaped by the role of religious leaders and community figures who influence them over generations. Discussion. Religious leader and community figures shaped communication in one-way communication.  Adopted a hypodermic theory, the hypodermic needle model (known as the hypodermic-syringe model, transmission-belt model, or magic bullet theory) is a model of communication suggesting that an intended message is directly received and wholly accepted by the receiver (Raddock, 2011). Despite of the said model had been used for mass-communication process, the hypodermic needle is suitable for the process in interpersonal communication when the sender deliver messages about loudspeaker-ban through generations.  There have been no feedback nor discussion from the receiver.  The communities agree with the power of messages spread by religious and communities figures about their what-so-called traditional values.  Keywords :  One-way communication – hypodermic needle, loudspeaker ban, traditional value